Digestive Medicine Research (DMR)—an international journal jointly founded by the Seventh Affiliated Hospital of Sun Yat-sen University and AME Publishing Company - Office, Editorial (Digestive Medicine Research, 2018)
On May 2, 2018, a strategic cooperative agreement was signed in Shenzhen by the Seventh Affiliated Hospital of Sun Yat-sen University and AME Publishing Company, which announced both parties to jointly found an international academic journal Digestive Medicine Research (Dig Med Res; DMR).